Impact of varying the parameters of stimulation of 2 commonly used waveforms on muscle force production and fatigue - Lein, D. H.; Myers, C.; Bickel, C. S. (Journal of Orthopaedic & Sports Physical Therapy, 2015)
Study Design: Laboratory based experimental study using a repeated-measures design.